1989
DOI: 10.3109/02844318909067504
|View full text |Cite
|
Sign up to set email alerts
|

Microvascular Anastomosis of Interpositional Vein Grafts with the Unilink System: A Comparative Experimental Study

Abstract: Vein segments from the posterior facial vein of the rabbit were surgically isolated and re-anastomosed, either by manual suture technique or by the use of a new mechanical anastomotic device, the UNILINK apparatus. The purpose of the study was to compare anastomotic patency and time required for an orthotopic vein grafting procedure, when the two techniques were used. In the grafts anastomosed with the UNILINK technique, both clinical and histological evaluation showed 100% patency, while 20% of the sutured gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
13
0

Year Published

1989
1989
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 10 publications
0
13
0
Order By: Relevance
“…The 3M Precise Microvascular Anastomotic Device has been tested extensively in animals and humans 7–14 . We ourselves originally tested it by re‐anastomosing the inferior cava and aorta of a rat.…”
Section: Discussionmentioning
confidence: 99%
“…The 3M Precise Microvascular Anastomotic Device has been tested extensively in animals and humans 7–14 . We ourselves originally tested it by re‐anastomosing the inferior cava and aorta of a rat.…”
Section: Discussionmentioning
confidence: 99%
“…4,6,7 The mechanism leading to medial atrophy was thought to be arterial pressure against the rings. Berggren et al 4 have reported that the thickness of vessel wall was reduced to 10-20% of normal at the 16th week, and that vessel continuity was maintained just by intimal thickening Figure 6.…”
Section: Discussionmentioning
confidence: 99%
“…However, the rigid polyethylene rings remained permanently at the anastomotic site, leading to atrophy of the vessel wall. 4,6,7 To resolve this problem, we developed the absorbable pinned-ring device in 1991, and the anastomotic process was designed to be performed only by one person.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Unlike hand-sewn anastomoses, however, coupled veins require the implantation of a polyethylene/stainless steel device that may cause complications that are independent of vascular patency. For example, some patients have complained that the devices are annoying when palpable under the skin.…”
mentioning
confidence: 99%